Workload and musculoskeletal complaints on cap tikus farmers - Kelung, Shania Britney Nikita; Kawatu, Paul Arthur Tennov; Asrifuddin, Afnal (BKM Public Health and Community Medicine, 2023)
Objective: In general, farm workers use more muscle strength to work, so they are at a high risk of experiencing musculoskeletal complaints. Cap tikus farmers are also workers who use a lot of body muscle movements and receive a physical workload, which causes some cap tikus farmers to complain of musculoskeletal-related pain. This study aims to determine the workload and musculoskeletal complaints of cap tikus farmers. Methods: Descriptive research uses two research designs, namely a survey research design for the musculoskeletal complaints variable with 41 respondents and a case study research design for the workload variable with a total of two respondents. This research was conducted in Palamba Village, South Langowan Sub-district. The data were analyzed using univariate analysis. Results: Research on musculoskeletal complaints among cap tikus farmers found that 46.3% of respondents were at a low-risk level, 39% were at a moderate-risk level, and 14.65% were at a high-risk level. Based on the muscle parts, the most complaints of pain were felt in the right shoulder (58.5%), the right knee (48.8%), and the back (46.3%). Most painful complaints are felt in the back (22%). The results of the workload research were obtained at a moderate workload level of between >200-359 kcal/hour. Conclusion: Musculoskeletal complaints among cap tikus farmers were at a lower risk level. Based on the muscle parts, the most common complaints were on the right shoulder, the right knee, and the back. Meanwhile, the workloads were at a moderate level.